Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Suami Tentang Antenatal Care Di Wilayah Kerja Puskesmas Purwosari Kota Surakarta - Rahman, Arif; , Dr. Faizah Betty Rahayuningsih A, S.Kep., M.Kes (2017)
Background: Healthy pregnant women is one of the important aspects to be considered in a woman's life cycle because throughout pregnancy complications can occur that are not expected. Knowledge husband against pregnancy is needed to optimize the wife's health during pregnancy. The purpose of this research is to know the effect of health education on knowledge of Antenatal Care husband. Methods: This study is a quantitative research using pre-experimental design of type one group pretest posttest. The study population was all the husbands of pregnant women in Puskesmas Purwosari Surakarta. Research sample were 36 respondents obtained by purposive sampling technique. Collecting data using questionnaires, while data analysis using paired samples t-test. Results: Paired sample t-test knowledge gained t value 7.696 and the significant value of 0.000. Because pv value <0.05 (0.000 <0.05), the decision was taken the test is H0 rejected. The average value of knowledge is a pre-test and post-test 15.17 at 17.22. Conclusion: The study shows there is a significant influence on the increased knowledge about antenatal care husbands of pregnant women in the Puskesmas Purwosari Surakarta, where the average value of knowledge after health education was higher than before the health education, the provision of health education proved to be effective against the increase knowledge of antenatal care in pregnant mother's husband.